Пошаговое объяснение:
y + 1/3 = 1/2
У=1/2-1/3
У=3/6-2/6
У=1/6
1/3 - x = 1/12
Х=1/3-1/12
Х=4/12-1/12
Х=3/12=1/4
11/15 - c = 1/5
С=11/15-1/5
С=11/15-3/15
С=8/15
1/3 + a = 3/5
А=3/5-1/3
А=9/15-5/15
А=4/15
b- 1/15 = 2/5
В=2/5+1/15
В=6/15+1/15
В=7/15
c - 1/2 = 1/5
С=1/5+1/2
С=2/10+5/10
С=7/18
Пошаговое объяснение:
y + 1/3 = 1/2
У=1/2-1/3
У=3/6-2/6
У=1/6
1/3 - x = 1/12
Х=1/3-1/12
Х=4/12-1/12
Х=3/12=1/4
11/15 - c = 1/5
С=11/15-1/5
С=11/15-3/15
С=8/15
1/3 + a = 3/5
А=3/5-1/3
А=9/15-5/15
А=4/15
b- 1/15 = 2/5
В=2/5+1/15
В=6/15+1/15
В=7/15
c - 1/2 = 1/5
С=1/5+1/2
С=2/10+5/10
С=7/18